Age differences in consumer financial capability. (July 2015) - Xiao, Jing Jian; Chen, Cheng; Sun, Lei
Abstract The purpose of this study is to examine age differences in financial capability. Financial capability is measured by five variables: objective financial literacy, subjective financial literacy, desirable financial behavior, perceived financial capability, and a financial capability index. Financial capability is expected to increase with age. Specifically, we expect older consumers to demonstrate higher levels of both objective and subjective financial literacy, more desirable financial behaviors, a higher level of perceived financial capability, and a higher score on the financial capability index. Data from the 2012 National Financial Capability Study in the U.S. was used to examine the associations between age groups and financial capability variables. One‐way ANOVAs were used to examine age differences in financial capability variables. Then multiple regressions were used to examine age differences after controlling for socio‐demographic and financial variables. The results indicated that age differences in four financial capability variables showed similar patterns. Young adults aged 18–24 had the lowest scores on objective financial literacy, subjective financial literacy, perceived financial capability, and the financial capability index. The results have implications for consumer educators to provide effective financial education for all age groups.